Severe Vascular Complications Due to Liver Hydatid Cyst Relapse: A Case Report and Review of the Literature - Ramia JM; De La Plaza R; Kuhnhardt AW; Gonzalez JD; Valenzuela JC; Garcia-Amador C; Lopez-Marcano AJ (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Vascular complications of liver hydatidosis are infrequent but severe. We present a case with severe vascular problems due to a recurrence of a liver hydatid cyst. A 39 year-old male consulted the Emergency Department after frank hematemesis due to esophagealvarices. He had undergone surgery at the age of seven in his native country for liver and lung hydatid cysts. Abdominal CT showed a 20 cm multivesicular cyst, occupying segments IV, V and VIII of the liver, displacing and partially compressing a dilated portal vein and causing portal hypertension and obstruction of the inferior cava vein. A subtotal cystectomy was performed. After surgery, portal vein flow was normal and esophagealvarices disappeared, but caval obstruction remained. We review the vascular complications due to liver hydatidosis, focusing on therapeutic management.